What do we know about the future of food trade? - Glauber, Joseph W.; Gabriel, Sherwin (International Food Policy Research Institute, 2025)
Trade in agriculture and food products increased dramatically over the past 20 years, driven by population and income growth that resulted in consumption exceeding production in many countries. Productivity growth grew as well, allowing countries with surplus production to meet global import demand. Reforms in the global trading system have reduced import barriers, also encouraging trade.